Wiley Online Library. Issue 2 (3rd July 2021) - Perez, Jorge E.
Abstract: The Wiley Online Library allows access to multidisciplinary resources, such as journals, reference works, and e-books under one platform with nine overarching subject discipline areas including health and medical sciences. Users have several methods of searching and discovery, can download e-resources in PDF format, and can produce citations in many formats. Users are also able to track citations, add items to a favorites list, add certain e-resource alerts, and use a built-in copyright permission/usage tool named RightsLink ® . An administrator platform offers many acquisition packages types to choose from according to institutional needs. Subscribers also have access to other services, trainings, and support.